A SYSTEMATIC REVIEW OF SPARKOL VIDEOSCRIBE MEDIA IN TEACHING WRITING SKILL - Dwi Almatiana; Desi Sri Astuti; Yulia Ramadhiyanti (XXXX-XXXX, 2021)
The research aimed to investigate the contribution of using sparkol videoscribe media in teaching writing skill. This research reviewed the previous studies on sparkol videoscribe in teaching writing skill which were published within the past ten years. This research used systematic review as the method. The population of this research was eighteen studies, then it screened used flow charts based on inclusion and exclusion criteria. There were five studies as the sample. This research used indirect observation as a  technique and document analysis as the tools. To analyze the data, this research used thematic analysis as the technique analysis of data.  Based on the result of the review, the result indicated that (1) The use of sparkol videoscribe media helped the teacher in teaching writing skill. (2) The successful of using sparkol videoscribe media in teaching writing skill based on students’ achievement increased. (3) Sparkol videoscribe media encouraged students’ interest, motivation, activeness, and able to engage students’ attention. From the results above, the sparkol videoscribe media gave the contribution in teaching writing skill.Keywords: Systematic review, sparkol videoscribe, writing skill.